Carbon assessment for Robusta coffee production systems in Vietnam: a case study in Dak Lak - Nguyen-Duy, Nhiem; Talsma, Tiffany; Nguyen, Kien Tri; Do, Thanh Chung; D'Haeze, Dave; Läderach, Peter R.D. (2018)
Carbon assessments have proliferated to identify climate friendly practices in Arabica producing systems, though little attention is given to Robusta. In this study, we evaluated the climate impact of Robusta production via quantification of carbon stock and greenhouse gas (GHG) emissions in the intensive shaded and unshaded coffee farms of the world’s largest Robusta producing region, Vietnam’s Central Highlands. We find due to the linear relationship between fertilizer use and yields, emissions from input use on a per unit product basis are not significantly different between the intensive and less intensive systems. However, when accounting for carbon sequestered in shade and coffee trees, the less intensive systems are carbon positive (sequestering more than they emit) per unit of green coffee bean produced.